The role of service-induced residual stresses in initiating and propagating stress corrosion cracking (SCC) in a 316 stainless steel pressure-relief-valve nozzle set. (November 2019) - Abdul Jawwad, Abdul Kareem; Mahdi, Mofid; Alshabatat, Nabeel
Abstract: A full failure analysis was applied to a set of failed stainless steel (SS) nozzle and sealing disk. The set was taken from a pressure relief valve (PRV) installed on a piping carrying hydrocarbon gas. The investigation included both experimental and numerical analysis. Experimental analysis confirmed the failure mode in the present case to be high-stress-regime transgranular stress corrosion cracking (TGSCC) promoted by susceptible microstructure and the presence of a chloride- and H2 S-bearing working fluid. Finite element modelling (FEM) was used for the numerical analysis to model the evolution of tensile residual stress associated with the observed SCC. FEM results have shown that the tensile stresses, required for crack initiation and propagation, were associated with the service conditions, especially thermal history, of the nozzle set. FEM results have shown very close (almost exact) agreement with the experimental results obtained in terms of crack directions, relative stress levels and locations of dominance for each type of stress. The present results are thought to be very useful in designing/re-designing similar parts for better performance, under extreme thermal conditions, and for avoiding such failure in future. Highlights: FEM was used successfully to accurately model residual stresses. Local weather conditions can strongly affect parts' thermal history. SCC was initiated by service-induced residual stresses in 326 SS. SCC crack morphology is dependent on stress magnitude and direction.